Evaluating the implementation of the character education strengthening program of vocational high schools in Yogyakarta City - Edhy Susatya; Budi Santosa; Andriyani Andriyani; Dwi Ariyani (REID (Research and Evaluation in Education), 2021)
The research aims to evaluate the character education strengthening program (CESP) implementation in vocational high schools (VHS) throughout Yogyakarta City. The evaluation is done in the functions of (1) planning, (2) implementation, and (3) evaluation. In this descriptive qualitative research, the researchers collected information related to the implementation of CESP. The subjects are school principals, vice principals, and teachers determined using the snowball sampling technique in four vocational high schools in Yogyakarta City. The evaluation uses the discrepancy model, which looks for the gap between planning and implementation. Data were collected through observation, interviews, and documentation, validated using the source and collection triangulation, and analyzed using a descriptive technique carried out during and after completing data collection within a certain period. The findings show that: (1) the CESP planning consists of elements of initial assessment, CESP socialization, vision and mission, policy design, and CESP design, with an average score of 2.74, meaning that it is good; (2) the CESP implementation consists of the elements including CESP development in learning, school culture development, community participation, and implementation of the CESP main values, with an average score of 2.98, meaning that it is in a good category; and (3) the CESP evaluation has an average score of 2.50, meaning that it is in a good category. The results of this study are recommended as consideration for mapping the CESP implementation, determining education policies related to character education, developing CESP models, reference for character research, and as materials for discussions regarding character education.